2021
DOI: 10.2147/ijn.s333279
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Tumor Cell Hybrid Membrane-Camouflaged Nanoparticles for Enhancing Therapy Efficacy in Glioma

Abstract: Purpose Cell membrane-camouflaged nanoparticles (NPs) are drawing increasing attention because their surfaces acquire some characteristics of the cell membranes, making them a unique class of biomimetic materials for diverse applications. Modification of cell membrane or combination of different types of membranes can enhance their functionality. Methods We prepared platelet and tumor cell membrane camouflaged β-mangostin-loaded NPs, which were synthesized with platelet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In recent years, multifunctional hybrid cell membranes (HCMs) have begun to be used to fabricate HCMCNPs [ 108 , 109 ]. HCMs mostly employ two types of cell membranes to hybridize such that the HCMs possess unique biological functions.…”
Section: Cell Membrane Types Currently Being Used To Coat Nanoparticl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, multifunctional hybrid cell membranes (HCMs) have begun to be used to fabricate HCMCNPs [ 108 , 109 ]. HCMs mostly employ two types of cell membranes to hybridize such that the HCMs possess unique biological functions.…”
Section: Cell Membrane Types Currently Being Used To Coat Nanoparticl...mentioning
confidence: 99%
“…HCMs mostly employ two types of cell membranes to hybridize such that the HCMs possess unique biological functions. The types of HCMs for current applications in NDs are shown in Figure 3 , and they include neutrophils–macrophages [ 110 ], dendritic cells–cancer cells [ 108 ], erythrocytes–cancer cells [ 111 , 112 ], and platelets–cancer cells [ 109 ]. HCMCNPs inherit the advantages of various cell membranes and make up for the deficiencies of different cell membranes.…”
Section: Cell Membrane Types Currently Being Used To Coat Nanoparticl...mentioning
confidence: 99%
“…Recently, a large number of studies have reported the design of nanoparticles that mimic cell functions by using various biological membranes, thus mediating excellent antitumor therapy. Briefly, these membranes include (1) natural cell membranes, such as red blood cell membrane, [53][54][55][56] white blood cell membrane, 57,58 tumor cell membrane 55,59 and macrophage membrane, [60][61][62] (2) cell-secreted membrane structure, 63 such as exosome, 60,[64][65][66][67][68][69] bacterial outer membrane [70][71][72] and apoptotic body, 73 (3) membrane structure with particular protein expression or inclusions, [74][75][76] such as membrane expressed with tumor-targeting molecule, programmed death-ligand 1 (PD-L1) or programmed cell death protein 1 (PD-1), and (4) the hybrid membrane [77][78][79][80][81] formed by two or more kinds of the above membranes. Moreover, many studies have shown that if we combine anti-tumor drugs with biological membrane-based nanoparticles, we will get a better therapeutic effect than drug-free biological membrane-based nanomaterials.…”
Section: Xiaojie Wumentioning
confidence: 99%
“…In recent years, the function of biological cell membranes for drug delivery in vivo has been continuously expanded ( 30 ), and the cell membranes of red blood cells, platelets, macrophages and cancer cells have been used to manufacture drug delivery carriers ( 31 ). Extracellular vesicles (EVs) are derived from the cell membrane, can also regulate the transport of substances and information exchange between many cells ( 32 ).…”
Section: Introductionmentioning
confidence: 99%